2016
DOI: 10.7150/thno.13478
|View full text |Cite
|
Sign up to set email alerts
|

A Multifunctional Theranostic Nanoagent for Dual-Mode Image-Guided HIFU/Chemo- Synergistic Cancer Therapy

Abstract: High-intensity focused ultrasound (HIFU) is deemed to be a promising noninvasive therapeutic modality for cancers as well as non-neoplastic diseases. However, the accuracy of the technique in the diagnosis and treatment of tumors remains unsatisfactory. HIFU, when combined with multifunctional synergistic agents (SAs), has the potential to be of greater diagnostic and therapeutic efficacy. Here we describe a smart and multifunctional hollow mesoporous Prussian blue (HMPBs) theranostic nanoplatform, the hollow … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
72
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 88 publications
(74 citation statements)
references
References 36 publications
2
72
0
Order By: Relevance
“…[10, 16] In addition, intense HIFU doses can damage the healthy tissue and cause off-target effects such as skin burns and nerve injury. [17, 18] More importantly, the volume of ablation after treatment with current HIFU methods is relatively large (typically cigar-shaped with dimensions on the order of 1–3 mm × 8–15 mm) and ablates tissue nonspecifically. [1] Thus, HIFU is often not suitable for treating small tumor nodules and micrometastases.…”
mentioning
confidence: 99%
“…[10, 16] In addition, intense HIFU doses can damage the healthy tissue and cause off-target effects such as skin burns and nerve injury. [17, 18] More importantly, the volume of ablation after treatment with current HIFU methods is relatively large (typically cigar-shaped with dimensions on the order of 1–3 mm × 8–15 mm) and ablates tissue nonspecifically. [1] Thus, HIFU is often not suitable for treating small tumor nodules and micrometastases.…”
mentioning
confidence: 99%
“…The Ser/ICG@lip optical property assay showed that this liposome could be used for dual‐modality NIR/PA imaging, which is a highly sensitive and non‐invasive technique. Compared with a single imaging mode, dual‐mode imaging can combine imaging advantages to accurately monitor and evaluate the phototherapeutic process (Cai & Chen, ; Zhang, Wang, et al, ; Zhang, Cai, et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…The Ser/ICG@lip optical property assay showed that this liposome could be used for dual-modality NIR/PA imaging, which is a highly sensitive and non-invasive technique. Compared with a single imaging mode, dual-mode imaging can combine imaging advantages to accurately monitor and evaluate the phototherapeutic process (Cai & Chen, 2008;Zhang, Cai, et al, 2016). The tumor vascular system is highly permeable, allowing access to liposomes smaller than 500nm to spread outside the blood vessels into the tumor interstitial space (Lombardo, Calandra, Barreca, Magazu, & Kiselev, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Wang et al reported a thermosensitive hydrogel (called BT-CTS thermogel) that had synergistic PTT/PDT anticancer effect and tissue regenerative activity to facilitate surgical wound healing. [334][335][336][337][338] Applying MRI to HIFU facilitated tumor imaging and IGS. [271,273,274,277,278,332] Zhang et al designed a cisplatin-loaded GERT (C-GERT) combining intraoperative PTT and chemotherapy for patients with advanced ovarian tumors.…”
Section: Other Synergistic Surgerymentioning
confidence: 99%